KOMUNIKASI PEMASARAN PERUSAHAAN PASCA PANDEMI : STUDI RESPON PELANGGAN TERHADAP PESAN DI INSTAGRAM - Purnomo, Agustina Multi; Pratidina, Ginung; Setiawan, Muhamad Fajar (JURNAL KOMUNIKATIO, 2022)
Companies were starting to fix the impact of the pandemic by carrying out various marketing communication strategies. Instagram was still the choice of marketing communication media after the Covid-19 pandemic. This study examined the marketing communication strategy by IPC Residence on Instagram to strengthen the company's post-pandemic promotions. The study examined respondents' responses to four factors of marketing communication in social media: communication, context, connectedness, and collaboration. The research used quantitative methods with questionnaire data collection tools. Collecting data on 100 respondents and measuring the Weight Mean Score found an average value of 4.49 on the four marketing communication factors in social media. The characteristics of the respondents represented the diversity and representativeness of the characteristics of customers and prospective customers of IPC Residence. The results indicated that IPC Residence has successfully carried out marketing communications through Instagram. These results denoted the company's hope for an excellent recovery after the Covid-19 pandemic.